Effect of Highly Active Antiretroviral Therapy (HAART) and Menopause on Risk of Progression of Cervical Dysplasia in Human Immune-Deficiency Virus- (HIV-) Infected Women - Suk Chul Kim; Susan Messing; Krupa Shah; Amneris E. Luque (Hindawi Limited, 2013)
Background. More HIV-infected women are reaching older age and menopause, but there is limited information on cervical squamous intraepithelial lesions (SILs) on these women. Methods. To assess the effect of HAART and menopause on SILs in HIV-infected women, we reviewed the results of Papanicolaou (Pap) tests obtained between 1991 and 2011 on 245 women. Progression to SILs was determined by comparing Pap test results. The association of HAART and transition to menopause on SILs was assessed using survival analysis. Results. Women receiving HAART had a 52% reduced risk in the progression to SILs compared to women receiving any other antiretroviral regimen or no regimen (CI: 0.33-0.70, P=0.0001). A greater increase of CD4+ cell counts was associated with a greater reduction on the risk of progression to SILs. Menopausal women had a 70% higher risk of progression to SILs than premenopausal women (CI: 1.11-2.62, P<0.0001), adjusting for HIV medications, CD4+ count, duration of HIV infection, moderation effect of menopause by age, prior IV drug use, and smoking. Conclusion. HAART had a positive long-term effect on the progression to SILs. However, being younger and menopausal increases the risk of progression.